2015
DOI: 10.1007/s00269-015-0763-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling defects and plasticity in MgSiO3 post-perovskite: Part 2—screw and edge [100] dislocations

Abstract: In this study, we propose a full atomistic study of [100] dislocations in MgSiO3 post-perovskite based on the pairwise potential parameterized by Oganov et al. (Phys Earth Planet Inter 122:277–288, 2000) for MgSiO3 perovskite. We model screw dislocations to identify planes where they glide easier. We show that despite a small tendency to core spreading in {011}, [100] screw dislocations glide very easily (Peierls stress of 1 GPa) in (010) where only Mg–O bonds are to be sheared. Crossing the Si-layers results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Full atomic modeling of [100] (Goryaeva et al 2015b) and [001] dislocation glide (this study) in MgSiO 3 postperovskite under lower mantle conditions demonstrates easy slip in (010) plane parallel to the structural layering. Being characterized by significantly different crystal chemistry, Mg-O and Si-O layers in the high-pressure MgSiO 3 phase lead to a very strong plastic anisotropy with (010) concentrating most of plastic shear.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Full atomic modeling of [100] (Goryaeva et al 2015b) and [001] dislocation glide (this study) in MgSiO 3 postperovskite under lower mantle conditions demonstrates easy slip in (010) plane parallel to the structural layering. Being characterized by significantly different crystal chemistry, Mg-O and Si-O layers in the high-pressure MgSiO 3 phase lead to a very strong plastic anisotropy with (010) concentrating most of plastic shear.…”
Section: Discussionmentioning
confidence: 84%
“…Being characterized by a larger Peierls stress of 3 GPa, the mobility of screw dislocations is expected to govern plastic strain for this slip system. However, it is worth noticing that, in contrast to [100] dislocations in post-perovskite (Goryaeva et al 2015b), where the Peierls stress σ p is found to be one order of magnitude lower for edge dislocations than for screw, σ p of edge dislocations is only 33% lower in case of the [001](010) system (Table 1).…”
Section: Lattice Frictionmentioning
confidence: 96%
See 3 more Smart Citations